COL11A1‐driven positive feedback loop modulates fibroblast transformation and activates pancreatic cancer progression. (2nd March 2023) - Sun, Defeng; dai, Tu; Ji, Yuan; Shen, Weibo; Bian, Wuyang
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most common leading causes of cancer death. The cancer‐associated fibroblasts (CAFs) in the tumor microenvironment (TME) aggravate the malignant behavior of PDAC. However, it is still unknown how PDAC induces normal fibroblasts (NFs) to CAFs. In present research, we found that PDAC‐derived collagen type XI alpha 1 (COL11A1) promoted the conversion of NFs to CAF‐like cells. It included morphological and corresponding molecular marker changes. Activation of the nuclear factor‐κB (NF‐κB) pathway was involved in this process. Corresponding, CAFs cells could secrete interleukin 6 (IL‐6), which promoted the invasion and the epithelial‐mesenchymal transition of PDAC cells. Furthermore, IL‐6 promoted the expression of transcription factor Activating Transcription Factor 4 by activating the Mitogen‐Activated Protein Kinase/extracellular‐signal‐regulated kinase pathway. The latter directly promotes the expression of COL11A1. This way, a feedback loop of mutual influence was constructed between PDAC and CAFs. Our research proposed a novel concept for PDAC‐educated NFs. PDAC‐COL11A1‐fibroblast‐IL‐6‐PDAC axis might contribute to the cascade between PDAC and TME.